Decoding plasma cell maturation dynamics with BCMA - Schulz, Sebastian R.; Menzel, Shannon R.; Wittner, Jens; Ulbricht, Carolin; Grofe, Alina T.; Roth, Edith; Mann-Nüttel, Ritu; Scheu, Stefanie; Kueh, Andrew J.; Jäck, Alexander; Herold, Marco J.; Hauser, Anja E.; et al. (Frontiers in Immunology, 2025)
Plasma cells provide protective antibodies following an infection or vaccination. A network of intrinsic and extrinsic factors fine-tunes the generation of a heterogenous plasma cell pool with varying metabolic requirements, transcriptional profiles and lifespans. Among these, the B cell maturation antigen (BCMA) has been implicated in the APRIL-mediated survival of long-lived plasma cells. To characterize the terminal maturation of plasma cells, we constructed a BCMA reporter mouse (BCMA:Tom) that exclusively labeled antibody-secreting cells and revealed that BCMA:Tom expression varied by IgH isotype and increased with plasma cell maturity. The BCMA reporter, used alongside the Blimp1-GFP reporter, also allowed detailed tracking of plasma cell development and highlighted the importance of the in vivo microenvironment to complete plasma cell maturation. Therefore, the BCMA:Tom reporter mouse provides a valuable tool for tracking plasma cell development and maturation with flow cytometry or advanced imaging techniques, enabling a deeper understanding of the mechanisms regulating plasma cell heterogeneity and longevity.